Polyorchidism with lobulation and septa in supernumerary testis - Bozgeyik, Zuelkif; Kocakoc, Ercan; Ozturk, Tulin (Aves, 2008)
Polyorchidism is a rare anomaly of the genitourinary system which is defined as the presence of more than two testes within the scrotum. Lobulation of a testis is also a rare anomaly. To the best of our knowledge, this is the first report of polyorchidism with lobulation of a supernumerary testis. We present ultrasonography findings of lobulation of a supernumerary testis in a 38-year-old man.
Keywords: polyorchidism; lobulation; septa; ultrasonography